Exploring Awareness and Understanding of Breast Cancer Risk Factors, Screening, and Treatment among Females in Pakistan - Nazir, Nosheen; Iftikhar, Iftikhar; Yaqoob, Hureem; Akhtar, Jahanzeb; Farooq, Fatima; Rehman, Zia Ur; Zahid, Rabia; Lolai, Aftab Ahmed; Murtaza, Ghulam (International Journal of Health Sciences, 2024)
Purpose: Breast cancer is a pressing concern in Pakistan, ranking as the second leading cause of death among women. Despite its increasing incidence, it often lacks adequate attention from policymakers and healthcare professionals. This oversight could have severe consequences. To effectively tackle this health crisis, a thorough understanding of breast cancer's prevalence, risk factors, diagnosis, treatment, and outcomes in Pakistan is crucial. Methodology: To assess the level of awareness and understanding of breast cancer among women, this study was conducted. A cross-sectional survey was conducted in the outpatient department of Fauji Foundation Hospital, Rawalpindi, involving 350 female patients. Data were collected using a pre-structured questionnaire and analyzed using SPSS Version 16.0. Findings: Descriptive statistics were used, and the results were expressed as percentages and presented graphically. The study found that 70% of women were aware of breast cancer. Furthermore, 74% of the patients were married, and 87% had children. Knowledge about signs, symptoms, diagnosis, and treatment of breast cancer was relatively high among the women surveyed. However, only 23% of women had knowledge about performing breast self-examinations, and 18% had heard about mammography. This study provides valuable insights into breast cancer awareness and prevention behaviors among women in Pakistan, with significant implications for theory, policy, and practice. The findings highlight gaps in knowledge and awareness, particularly regarding breast self-examinations and mammography screenings. Unique Contribution to Theory, Policy and Practice: Policy implications stemming from the study results include the need for targeted awareness campaigns, educational programs, and screening initiatives to improve breast cancer awareness and preventive behaviors among women in Pakistan. Policymakers should allocate resources towards these efforts and integrate breast cancer education into existing healthcare services and community outreach programs to ensure widespread dissemination of information and access to screening services.